Molecular Imaging of Aortic Valve Stenosis with Positron Emission Tomography - Reindert F. Oostveen; Yannick Kaiser; Erik S.G. Stroes; Hein J. Verberne (MDPI AG, 2022)
Aortic valve stenosis (AVS) is an increasingly prevalent disease in our aging population. Although multiple risk factors for AVS have been elucidated, medical therapies capable of slowing down disease progression remain unavailable. Molecular imaging technologies are opening up avenues for the non-invasive assessment of disease progression, allowing the assessment of (early) medical interventions. This review will focus on the role of positron emission tomography of the aortic valve with 18F-fluorodeoxyglucose and 18F-sodium fluoride but will also shed light on novel tracers which have potential in AVS, ranging from the healthy aortic valve to end-stage valvular disease.